Epistemological and didactic valuation of professional competencies - Abambari Arévalo , M. Sc. Mario Jacinto (Transformación, 2024)
The introduction of competency-based approach is not only a new expression of learning outcomes, but also for its epistemological and pedagogical implications leading to a transformation of the educational process and its evaluation. Today, this is an extremely controversial topic due to divorce between university curricula recognized competency, its realization in the teaching-learning process and how evaluated is practiced. It is therefore of utmost importance to achieve a thematic approach about the topic, for the reason that, while theorizing from process competences development is not new, it is so from the perspective of the considerations about how to evaluate performances and evidences. The results of this study contributed to provide a strategy to fulfill this purpose.
Keywords: competence development; competence assessment; professional problem solving